Особенности кормовых связей хальцид семейства Eurytomidae (Hymenoptera, Chalcidoidea) - Зерова, М.Д. (Вестник зоологии, 1971)
The article generalizes the results of studying the alimentary connections of chalcidsof the family Eurytomidae, as a result of which some regularities are established in the biological specialization of the family. A deep dependence of phytophagous forms on plants-hosts is detected which determines the ways of development of some groups of phytophages. For parasitic species two main tendencies of biological specia'ization arc observed: phylogenetic and morpho-typical specializations.